Ukrainian Issues in Geopolitical Thought of the Twentieth and Twenty-first Centuries - Reginia-Zacharski, Jacek (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
Ukrainian lands in the twentieth and twenty-first centuries have been in proximity of great geopolitical changes several times. During that time the Ukrainian nation – due to various factors – encountered a number of “windows of opportunity” for achieving the realization of dreams about independence and national sovereignty. The author identified in the period considered four “general moments,” of which two have been completed successfully. The first of these occurred in 1990–1991, when for the first time in modern history, Ukrainians managed to achieve a lasting and relatively stable independence. The second of the “moments” – still unresolved – are events that began in the late autumn of 2013. The process, called “Revolution of Dignity”, represents a new quality in the history of the Ukrainian nation, therefore, that the Ukrainians have to defend the status quo (independence, territorial integrity, sovereignty, etc.) but not to seek to achieve an independent being. The analysis leads to the conclusion that the ability of Ukrainians to achieve and maintain independence is largely a function of the relative power of the Russian state as measured with respect to the shape and quality of international relations.